Solar Water Disinfection to Produce Safe Drinking Water: A Review of Parameters, Enhancements, and Modelling Approaches to Make SODIS Faster and Safer - Ángela García-Gil; Rafael A. García-Muñoz; Kevin G. McGuigan; Javier Marugán (Molecules, 2021)
Solar water disinfection (SODIS) is one the cheapest and most suitable treatments to produce safe drinking water at the household level in resource-poor settings. This review introduces the main parameters that influence the SODIS process and how new enhancements and modelling approaches can overcome some of the current drawbacks that limit its widespread adoption. Increasing the container volume can decrease the recontamination risk caused by handling several 2 L bottles. Using container materials other than polyethylene terephthalate (PET) significantly increases the efficiency of inactivation of viruses and protozoa. In addition, an overestimation of the solar exposure time is usually recommended since the process success is often influenced by many factors beyond the control of the SODIS-user. The development of accurate kinetic models is crucial for ensuring the production of safe drinking water. This work attempts to review the relevant knowledge about the impact of the SODIS variables and the techniques used to develop kinetic models described in the literature. In addition to the type and concentration of pathogens in the untreated water, an ideal kinetic model should consider all critical factors affecting the efficiency of the process, such as intensity, spectral distribution of the solar radiation, container-wall transmission spectra, ageing of the SODIS reactor material, and chemical composition of the water, since the substances in the water can play a critical role as radiation attenuators and/or sensitisers triggering the inactivation process.